“Post-COVID syndrome”: The focus is on musculoskeletal pain - A. E. Karateev; V. N. Amirdzhanova; E. L. Nasonov; A. M. Lila; L. I. Alekseeva; E. Yu. Pogozheva; E. S. Filatova; V. A. Nesterenko (Научно-практическая ревматология)
Combating the consequences of COVID-19, a disease caused by the new coronavirus infection SARS-CoV-2, is a serious and very urgent task facing modern medicine. COVID-19 often has a severe course and is accompanied by multiple organ damage, systemic immune inflammation, coagulopathy, neuroendocrine and metabolic disorders. Even with a relatively favorable course, the consequences of SARS-CoV-2 infection can be degenerative changes in many organs (pulmonary fibrosis, cardiosclerosis), various functional and psychoemotional disorders. As a result, in 10–50% of patients, various unpleasant symptoms persist for a long time after the acute manifestations of COVID-19 subside and the virus is eliminated. This pathology is referred to as “post-COVID syndrome” (PCS). The main elements of PCS are chronic pain, fatigue, and psychoemotional problems. Functional disorders, autoimmune processes, and severe psychological distress after COVID-19 can cause the development and exacerbation of diseases characterized by chronic pain and fatigue, such as fibromyalgia and chronic fatigue syndrome. Therapy and prevention of PCS include correction of functional disorders, pain control, and consistent physical, psychological, and social rehabilitation.